2014
DOI: 10.3280/fr2014-001002
|View full text |Cite
|
Sign up to set email alerts
|

The relation between R&D accounting treatment and the risk of the firm: Evidence from the Italian market

Abstract: In this paper, we investigate the relation between the different accounting treatments of R&D expenditures and the risk of the entity in order to identify under which treatment insiders are more likely to carry out earnings management. By analysing the R&D investment strategies of a sample of 137 listed Italian entities that complied with the requirements of IAS 38 during fiscal year 2009, following Lantz and Sahut (2005), we calculate several indexes that show the preferences of insiders to account R&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…R&D investment would occupy more resources, bringing many uncertainties, such as the loss of investment opportunities. This inevitably brings corresponding financial pressures ( 11 ). Huang et al ( 12 ) adopted individual random effect model to verify the relationship between R&D investment and risk, and the research results showed that R&D investment and bankruptcy risk was significantly positive correlation.…”
Section: Introductionmentioning
confidence: 99%
“…R&D investment would occupy more resources, bringing many uncertainties, such as the loss of investment opportunities. This inevitably brings corresponding financial pressures ( 11 ). Huang et al ( 12 ) adopted individual random effect model to verify the relationship between R&D investment and risk, and the research results showed that R&D investment and bankruptcy risk was significantly positive correlation.…”
Section: Introductionmentioning
confidence: 99%